Creative Youth Against Unemployment: Strengthening Community-Based Social and Entrepreneurial Skills in Bone Regency, South Sulawesi - Asrijal, Andi; Zulkifli , Zulkifli; Indrawati, Ajeng R (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effectiveness of the Community Empowerment Program (PKM)